Effect of Ethical Procurement Practices on Performance of Commercial State Corporations in Kenya - Maina, Stephen; Mburu, David; Ngunyi, Anthony (International Journal of Supply Chain Management, 2025)
Purpose: Procuring commodities and service is a critical avenue for delivery of public services by the state in any country. Process integrity right from need identification, tendering and eventual provision of services and works or delivery of the goods and their utilization is significant in identifying how robust public service is. Notably, challenges afflict ethical procurement practices in the public sector, leading to public resources losses along the supply chain. Thus, this study’s main goal was to evaluate the relationship between ethical procurement practices and performance of Kenya’s commercial state corporations. Methodology: Descriptive research design was used to study 165 Supply Chain Management staff at the targeted 33 functional corporations. Data was compiled through questionnaires. Pilot study was done to ensure reliability and validity of research instruments. The data was analyzed by use of descriptive statistics that included analysis of frequency, percentages, mean and standard deviation. Inferential statistics were further applied to assess the degree of relationship among the study variables, and results presented through tables and charts. Findings: The study results indicated a positive and significant relationship between ethical procurement practices (tendering, contracting and sourcing) and performance of commercial state corporations. However, ethical practices in specifications development did not have a significant effect. The study therefore concludes that ethical practice in tendering, sourcing and contracting significantly directly affected commercial state corporations’ performance. Unique Contribution to Theory, Practice and Policy: The study recommended that commercial state corporations should invest in staff capacity building on specifications development, inherent ethical standards/practices and their significance in order to improve quality service delivery to the public.